2020
DOI: 10.1371/journal.pone.0233994
|View full text |Cite
|
Sign up to set email alerts
|

The geography of sentiment towards the Women’s March of 2017

Abstract: The Women's March of 2017 generated unprecedented levels of participation in the largest, single day, protest in history to date. The marchers protested the election of President Donald Trump and rallied in support of several civil issues such as women's rights. "Sister marches" evolved in at least 680 locations across the United States. Both positive and negative reactions to the March found their way into social media, with criticism stemming from certain, conservative, political sources and other groups. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 31 publications
0
32
0
1
Order By: Relevance
“…We develop a classifier that we apply to the sentiment analysis of the content of the entire tweet message, which includes one of the two key words (Felmlee, Blanford et al 2020; Felmlee, Inara Rodis et al 2020; Zhang and Felmlee 2017). The sentiment tool is a variation of the VADER (Valence Aware Dictionary and Sentiment Reasoner) classifier.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We develop a classifier that we apply to the sentiment analysis of the content of the entire tweet message, which includes one of the two key words (Felmlee, Blanford et al 2020; Felmlee, Inara Rodis et al 2020; Zhang and Felmlee 2017). The sentiment tool is a variation of the VADER (Valence Aware Dictionary and Sentiment Reasoner) classifier.…”
Section: Methodsmentioning
confidence: 99%
“…Prior research finds that it takes an average of 24 seconds to 1.5 minutes to locate the first of thousands of derogatory, aggressive tweets, on the basis of a sample of searches for assorted defamatory slurs and insults (e.g., n**ger , who*e , fa**ot ) (Sterner and Felmlee 2017). Additional research on sexist tweets identified more than 419,000 tweets per day that included at least one of four sexist slur words ( bi*ch , c**t , s**t , and who*e ) during a one-week collection period (Felmlee et al 2020). Such negative messages often can be retweeted or “liked” by followers, thereby creating networks of cyberbullying that spread far beyond the original perpetrator and target (Felmlee et al 2018).…”
Section: Online Harassment On Social Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…Other research [37] even found a partly negative correlation between happiness and health, i.e., the happier, the unhealthier. At the scale of entire cities, [38] conducted a massive study on the relationship between "Twitter happiness" and demographic and place characteristics, and [39] investigated nation-wide sentiments towards a historic event (Women's March 2017).…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, the widespread and well-established advantages of network modeling approaches on hashtags [13,14,28,29] or users [30,31] in recent literature analyzing protests based social media data, they are often not capable of handling the complexity of the sentiment, temporal, and spatial patterns of these actions in one approach. One limitation is that the analysis relies on Tweets having coordinates as an inherent part of the dataset [32,33], which-according to earlier studies-represents only a small subset of all tweets (approximately 1-10%) posted within a specified time period [34]. Another limitation is that they focus only on a single language (usually English) that may also limit the spatial interpretability of the results [35], especially in the case of movements that span over multiple countries.…”
Section: Related Workmentioning
confidence: 99%